Terek O.I. Plant growth and development: textbook / O.I. Terek, O.I.Patsula. – L’viv: Ivan Franko LNU, 2011. – 328 p. (review) - колегія, редакційна (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Terek O.I. Plant growth and development: textbook / O.I. Terek, O.I.Patsula. – L’viv: Ivan Franko LNU, 2011. – 328 p. (review)